Ernesto DELGADO, "Pálpito". Madrid, Visor, 2024, 50 pp. - Egido, Aurora (Tropelías: Review of Literary Theory and Comparative Literature, 2024)
Ernesto DELGADO, "Pálpito". Madrid, Visor, 2024, 50 pp.
Keywords: Ernesto Delgado; Pálpito